Hybrid simulation for obstetrics training: A systematic review. (March 2020) - Le Lous, Maela; Simon, Ombeline; Lassel, Linda; Lavoue, Vincent; Jannin, Pierre
Abstract: Hybrid simulation is defined as the use of a patient actor combined with a task trainer within the same session. We sought to investigate the level of evidence about the clinical benefits of hybrid simulation training in obstetrics. We searched MEDLINE using the keywords: Obstetrics AND Medical Education AND (Standardized patient OR Hybrid simulation). A total of 155 studies were screened, from which we selected 11 articles were selected from the title and the abstract in PubMed. For each study, data about the type of simulation, the level of evidence according KirkPatrick's hierarchy was collected. There is evidence that clinical benefit for patients exists for Shoulder Dystocia, and Cord prolapse. For Non-technical skills, such as communication or team training, hybrid simulation was also effective. Whether hybrid simulation offers better training for communication and better immersion than high-fidelity simulation for learners remains to be investigated.